IMPACT OF LEGAL REGULATIONS ON THE CAPITAL MARKET IN CONNECTION WITH THE DEVELOPMENT OF BLOCKCHAIN TECHNOLOGY - Szutko, Sylwia (Człowiek w cyberprzestrzeni, 2020)
Blockchain technology is beginning to play a significant role in the capital market area. The National Depository for Securities completes works on the Blockchain Platform for the Capital Market, which is to be an open and fully secure infrastructure for the capital market, supporting solutions in the field of post-transaction services. One of its most important applications is to be eVoting application providing support for general meetings.